The Influence of Various Factors on the Deflections and Strength of Profiled Sheeting at the Stage of Concreting a Steel-Reinforced Concrete Slab - Yu. A. Shaposhnikova (Железобетонные конструкции, 2024)
The aim of the work was to study the influence of the span, slab thickness, grade and thickness of the corrugated sheet on the deflections of the profiled sheeting at the concreting stage of the composite slab. The object of the study was orthotropic composite slabs made using on permanent formwork in the form of profiled sheeting of grades H75, H144, H153 according to GOST 24045–2016 and TRP200 according to GOST R 52246, with a thickness of 0.7–1.5 mm. A calculation and analytical method of research was used, based on regulatory documents in force in the Russian Federation. Based on the results of the study, the influence of deflections and strength of the corrugated sheeting on the applicability of various spans of corrugated sheeting in the range from 3 to 6 m at the concreting stage of the composite slab was analyzed. Recommendations are proposed to limit the use of small thicknesses of corrugated sheets of 0.7–1.0 mm for spans over 4 m for slabs less than 250 mm thick with grades of corrugated sheets H114 and H153 according to GOST 24045–2016. Recommendations are given for the installation of temporary inventory supports for all spans of composite concrete floors when using corrugated sheets of 0.7–0.9 mm thickness for grade H75 according to GOST 24045–2016. The obtained data can be used in the design of composite concrete floor slabs and in the inspection of the technical condition of erected structures.